Surface-engineered N-doped carbon nanotubes with B-doped graphene quantum dots: Strategies to develop highly-efficient noble metal-free electrocatalyst for online-monitoring dissolved oxygen biosensor - Wang, Yu-Xuan; Rinawati, Mia; Huang, Wei-Hsiang; Cheng, Yao-Sheng; Lin, Pin-Hsuan; Chen, Kuan-Jung; Chang, Ling-Yu; Ho, Kuo-Chuan; Su, Wei-Nien; Yeh, Min-Hsin (Carbon (New York), 2022)
Dissolved oxygen (DO) is an essential indicator for evaluating water quality, the exquisitely sensitive electrochemical DO sensor could accurately record response which was based on oxygen reduction reaction (ORR) with a sluggish reaction rate. Thus, high-efficient ORR electrocatalysts are urgently needed for broad applications. As a matter of fact, graphene quantum dots (GQDs) have attracted a great deal of attention, several heteroatoms are extensively introduced in GQDs fragments to regulate their inherent chemical and electrical properties by adjusting their electronic structure. However, B–N–C moieties always exist for some BN-codoped carbons due to the intermolecular force that might prohibit its electrocatalytic activity. Therefore, this research design a strategy to solve this problem; despite substantial efforts, this study shows a metal-free B-doped GQD/N-doped carbon nanotubes (BGQD/NCNTs) electrode significantly influences ORR electrocatalytic activity due to the synergistic effect and abundant active sites. Herein, BGQD/NCNTs exhibit an excellent ORR performance with an onset potential of 0.91 V (vs. RHE), exceeding most reported GQDs-introduced electrocatalysts; it also outperformed the commercial electrocatalyst in terms of long-term stability. For seawater DO sensing, BGQD/NCNTs exhibit ultra-high sensitivity of 0.011 mA/cm2ppm and further integrate into an online detection platform to accomplish the aim of continuous monitoring via a wireless connection. [Display omitted] •A novel strategy to lower B–N moieties in B,N-codoped carbon based electrocatalyst was proposed.•BGQDs/NCNTs display better onset potential toward ORR than pristine CNTs.•BGQD/NCNTs shows promising sensitivity and stability for dissolved oxygen sensing in seawater.•The aim of continuous online monitoring was achieved via a wireless connection.